Freedom as a natural ability in Roman law - Bronisław Sitek (Journal of Modern Science)
Objectives The subject of this study is the issue of perception of individual freedom by Roman lawyers. It is generally accepted that slaves were treated as property. However, in order to understand what was the actual perception of slaves and slavery, it is necessary to analyze selected sources of law, especially such lawyers as: Florentinus, Ulpian. Marcianus or Hermogonianus. The institution of favor debitoris was also quite often used to resolve doubts about human freedom.